High doses of garlic extract significantly attenuated the ratio of serum LDL to HDL level in rat-fed with hypercholesterolemia diet. Issue 1 (December 2015) - Ebrahimi, Tahereh; Behdad, Behnoosh; Abbasi, Maryam; Rabati, Rahman; Fayyaz, Amir; Behnod, Vahid; Asgari, Ali
Abstract Background Hypercholesterolemia is associated with an increased risk of heart disease. In this study, we investigated the antihyperlipidemic effects of garlic (Allium sativum L.) in rat models of hypercholesterolemic. Methods Wistar male rats were randomly divided into 4 diet groups with garlic supplementation. Male Wistar rats were fed by standard pellet diet (group I), standard diet supplemented with 4 % garlic (group II), lipogenic diet (containing sunflower oil, cholesterol and ethanol) equivalent to 200 mg raw garlic/kg body weight (raw) (group III) and lipogenic diet equivalent to 400 mg raw garlic/kg body weight (raw) (group IV). Results Rats fed 400 g/kg garlic extract(GE), had a significantly lower concentration of serum low-density lipoprotein cholesterol (LDL-C) cholesterol and elevated HDL –C cholesterol at day 28 (P  < 0.05).In addition, serum levels of LDL-C was lower in the III and IV group than those in the IV group (P  < 0.001 for each). However, cholesterol efflux capacity was positively correlated with HDL cholesterol concentration (P  < 0 · 0001). It was also directly correlated with garlic supplementation (P  < 0 · 0001). Conclusion Together Taken, the results are clearly indicative of the beneficial effects of garlic in reducing lateral side effects of hyperlipidemia. Our data demonstrate that GE has protective effects on HDL in rats with high LDL intake. Therefore, it could be used to remedy hypercholesterolemia with help reduce risk of coronary heart disease Virtual slides The virtual slide(s) for this article can be found here:http://www.diagnosticpathology.diagnomx.eu/vs/1834155749171141